2015
DOI: 10.1007/s40472-015-0066-5
|View full text |Cite
|
Sign up to set email alerts
|

Treg Therapy in Transplantation: How and When Will We Do It?

Abstract: Adoptive therapy with regulatory T cells (Tregs) has shown great promises in many experimental models to induce permanent graft acceptance and tolerance to alloantigens. However, although their tolerogenic therapeutic potential has been demonstrated in clinical hematopoietic stem cell transplantation and partially in patients with early onset type I diabetes, translation into clinical testing for solid organ transplantation is still lacking or only slowly starting. This is in part due to the fact that many que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 98 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…T-cell subpopulations known as "regulatory T-cells (T regs )" are experts in controlling and suppressing the immune system. Previously, in mouse hepatic allograft models, it has been demonstrated that T regs play a significant role in spontaneous graft tolerance [104,105], and there is an increase in T regs proportion in patients who are spontaneously tolerant [106]. As a result, numerous strategies for making use of their innate abilities have been thoroughly researched.…”
Section: Supporting Cellsmentioning
confidence: 99%
“…T-cell subpopulations known as "regulatory T-cells (T regs )" are experts in controlling and suppressing the immune system. Previously, in mouse hepatic allograft models, it has been demonstrated that T regs play a significant role in spontaneous graft tolerance [104,105], and there is an increase in T regs proportion in patients who are spontaneously tolerant [106]. As a result, numerous strategies for making use of their innate abilities have been thoroughly researched.…”
Section: Supporting Cellsmentioning
confidence: 99%
“…The motivation for the development arTregs is to reduce off-target immunosuppression; however it is possible that enhanced local bystander suppression due to activation of large numbers of arTregs could lead to an increased risk of local infection or reactivation of latent viruses present within the graft, such as BK virus in renal allografts [70] .…”
Section: Safetymentioning
confidence: 99%
“…[ 14 ] Furthermore, spontaneous allogeneic organ tolerance, a phenomenon in which transplant recipients accept the allografts without the use of immunosuppressive regimen, has been observed in liver transplant recipients with elevated Treg levels. [ 15 ] Currently, most clinical trials of Treg‐therapies utilize systemic adoptive transfer of ex vivo expanded Tregs. [ 16 ] While this method has shown promising results in clinical trials, [ 17,18 ] ex vivo expansion of Tregs requires extremely time‐consuming and costly protocols to generate appropriate numbers of cells for clinically significant results, due to the low frequency of Tregs in human peripheral blood.…”
Section: Introductionmentioning
confidence: 99%